Derivation, integration and numerical analysis of the solution to the equilibrium equation under constrained torsion of a prismatic body (Acta Education, 2024)
The article presents an analysis of the numerical results of solving the problem of constrained torsion of a prismatic body (one side is reinforced) within the framework of the theory of elasticity (one-dimensional theory), finding the equilibrium equation, and integrating the resulting system of differential equations. The state of convergence of the solution based on the geometric and mechanical characteristics of the object under consideration is investigated.